Influence of Airport Factors and Mission Fuel Burn Optimised Aircraft Trajectories on Severity and Engine Life - Khani, Nqobile (Cranfield University, 2014)
The continuous growth of air transport has raised concerns about global aircraft fuel consumption, emissions and noise. Industry’s efforts have identified that to reduce future emissions and the impact of aircraft operations on the environment will require contribution from: a) New technologies with better efficiency b) Improved asset management and c) Greener manufacturing and recycling processes. This research falls under asset management and involves aircraft trajectory optimisation. Most aircraft trajectory optimisation studies concentrate on optimising fuel burn, emissions and noise. Fuel burn is the dominant contributor to operating costs. During the course of this work, no work was found to better understand from an operator’s perspective how the optimal solutions for minimising fuel burn and protecting the environment will impact on engine useful life and the engine operating costs. Also no work was found to understand how engine component degradation will impact on the optimised solutions for fuel burn and engine life. The contribution to knowledge from this research is a) the assessment of the impact of airport severity factors on engine life consumption and aircraft performance and b) the assessment and quantification of the change in engine life usage when optimising for flight mission fuel burn and the change in flight mission fuel burn when optimising for engine life usage; in both cases the effects of engine component degradation are considered and assessed. The trade-offs between mission fuel burn and engine life optimised trajectories are presented here for a clean (new) engine for three routes (London–Madrid, London–Ankara and London–Abu Dhabi). The engine life calculated was the HPT blade life and HPT disc life due to creep, fatigue and oxidation failure modes independent of each other. Mission fuel burn and engine life trajectory optimisation assessments were conducted to incorporate the effects of degradation after 3000, 4500 and 5250cycles of operation. Further assessments were made linking aircraft performance to airport severity factors for the clean engine, after 3000cycles and after 5250cycles. A techno-economic environmental risk assessment approach was used. The results indicate that airports at higher altitudes e.g. Cairo, suffer more severity due to higher operating temperatures, but benefit from less climb fuel burn and lower operating costs. The severity and fuel burn for take-off at airports with higher ambient temperatures was found to be more due to the higher operating temperatures required. The operating cost at these airports was thus higher. The fuel burn optimised trajectories were found to be achieved at higher operating temperatures with reduced blade life (due to creep, fatigue and oxidation). In particular, for London–Madrid, the blade creep and blade oxidation lives were found to reduce by -3.4% and -2.1% respectively. The blade oxidation life optimised trajectories showed increase in fuel burn of +3.6% and +4.9% for London–Madrid and London–Ankara respectively. The blade creep life optimised trajectories for London–Abu Dhabi were found to benefit from less fuel burn during climb. The disc creep life optimised trajectories showed benefit in fuel burn for London–Ankara and London–Abu Dhabi. The conclusions from the study are: High OAT and high altitude airports such as Abu Dhabi require higher operating temperatures which have severe consequences on the engine component life, fuel burn and emissions. Fuel burn optimised trajectories have a negative effect on the blade life due to creep, fatigue and oxidation due to higher maximum operating temperatures. However, the reduction in fuel burn outweighs the drop in life, thus benefitting to the operating costs. Optimising for blade creep life benefits the fuel burn for London–Abu Dhabi due to less fuel burn at climb The blade oxidation life optimised trajectories are detrimental to the fuel burn due to slower cruise speeds and more time spent at cruise and descent The disc creep life optimised trajectories benefit the fuel burn for London – Ankara and London–Abu Dhabi due to flying at higher cruise altitudes and burning less fuel. The recommendations from this research include making improvements to the framework such as a) Integrating the lifing methodologies because in reality the failure modes are not entirely independent of each other but do interact b) Develop and incorporate a diagnostics and prognostics tool to predict levels of degradation c) Using actual waypoints and incorporate horizontal trajectory profiles d) Future studies can include noise as an objective, which though mentioned has not been within the scope of this work. e) A key driver to lower operating costs is a considerable reduction in fuel burn. Maintenance costs will inevitably rise with engine life consumption. Further study of the trade-offs between fuel burn and engine life is therefore recommended.